Facile fabrication and characterization of novel three-dimensional halloysite nanotubes/graphene oxide composite aerogels for waste water treatment. (19th May 2018) - Hong-li, Liu; Ning, Wei; Xiang, He; Guo-qing, An; Yu-jie, Xuan
ABSTRACT: In order to develop efficient and environment benign sorbents for water purification, a simple hydrothermal process for fabrication of the halloysite (HNTs)/graphene oxide (GO) composite aerogels comprising HNTs anchored on graphene oxide sheets was developed. The morphology and structure of the materials were characterized by scanning electron microscopy (SEM), nitrogen adsorption-desorption, and Fourier transform infrared (FT-IR). The results demonstrated that the composites exhibit large surface area (SBET = 361.3778 m 2 ·g −1 ) and high pore volume (Vp = 1.2432 cm 3 ·g −1 ) with only 10 wt% of HNTs, higher than that of the ture GO aerogel (SBET = 142.8816 m 2 ·g −1, Vp = 0.6106 cm 3 ·g −1 ). The adsorption properties of the pure GO aerogels and n-HNTs/GO composite aerogels with 10 wt% of n-HNTs were measured using a UV-Vis spectrophotometer. The results reflected that the adsorptivity of MB by the n-HNTs/GO composite aerogels was 99.3%, much higher than the pure GO aerogels (89.4%).